A Moving Dune, A Stunning View: Visitors’ Recollections of a Ranger-Led Hike at Indiana Dunes National Park - Forist, Brian E.; Merson, Martha; Allen, Louise C.; Hristov, Nickolay I. (Frontiers in Education, 2021)
Interpretation in U.S. national park settings has experienced significant changes in both philosophy and practice in the 21st century. Interpreters are encouraged to co-construct audience-centered experiences, making space in their interactions for visitors’ knowledge, interests, and previous experience. Located 50 miles from Chicago, Indiana Dunes National Park thousands interact with rangers annually, many taking part in ranger-led walks. Researchers observed six ranger-led hikes and recruited a convenience sample for participation in a short survey to gather responses about interest and knowledge before the hike and a follow up phone interview. After ranger-led hikes, researchers conducted fifteen phone interviews using a phenomenological approach to glean visitors’ recollections of the experience. The study sought to answer questions about opportunities for science learning in national parks including: What do visitors recollect from their participation in ranger-led hike at Mount Baldy with a focus on landscape change, recent events, and associated scientific findings? What aspects of the interpretive experiences stand out as memorable? Our findings confirm that visitors arrive with background knowledge, scientific interests, and curiosity. Months after the park experience, they were able to give examples of change over time, the human effect on the landscape, and findings from recent scientific study at Mount Baldy. Interviewees recalled and reflected on rangers’ facilitation and props, as well as visual details and feelings evoked by the physical conditions. The results offer a rare look at what sticks with visitors after their participation in a ranger-led hike.